2010
DOI: 10.1182/blood.v116.21.2575.2575
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Utilization In a Tertiary Care Hospital: An Opportunity for Reduced Transfusion?

Abstract: 2575 Background: Use of platelet (plt) transfusions to treat and prevent bleeding varies widely between hospitals and by medical and surgical services. Standard indications include active bleeding with thrombocytopenia or plt dysfunction, pre or peri-invasive procedure, and prophylaxis for low plt counts. Rising demand for plt transfusions and donor shortage, coupled with the risks of transfusion (including infectious disease transmission and alloimmunization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This eliminates the cost of mechanical shakers and improves logistics handling during platelet shipping. Furthermore, recent investigations into the utilization of platelets for transfusion have shown that there is a significant increase in the need for therapeutic platelet transfusions compared to prophylactic transfusions [15,16]. With superior hemostatic functions and longer potential shelf life, CPs could be a promising product for actively bleeding patients.…”
Section: Introductionmentioning
confidence: 99%
“…This eliminates the cost of mechanical shakers and improves logistics handling during platelet shipping. Furthermore, recent investigations into the utilization of platelets for transfusion have shown that there is a significant increase in the need for therapeutic platelet transfusions compared to prophylactic transfusions [15,16]. With superior hemostatic functions and longer potential shelf life, CPs could be a promising product for actively bleeding patients.…”
Section: Introductionmentioning
confidence: 99%